Enhancing English Language Teaching and Learning: (An Examination of Research on Motivation and ELT Strategies for Arab EFL University Instructors) - Mohammed AbdAlgane; Prof. Omer Elsheikh Hago Elmahdi (Journal of Arts, Literature, Humanities and Social Sciences, 2025)
This study aims to examine the motivational factors and instructional strategies of Arab EFL university instructors. Comprehending the professional motivations of instructors and their pedagogical approaches can yield significant insights to effectively support their practices and improve student learning outcomes. A questionnaire was administered to 51 instructors to assess professional motivation and strategy use. Regarding motivation, results showed facilitating student learning and developing skills were primary drivers, enjoying intellectual challenges provided moderate motivation, while fulfillment from results least motivated instructors. For strategies, pair/group work and discussions emerged as most frequently employed, while grammar/vocabulary activities received neutral responses. The findings aligned closely with prior literature emphasizing intrinsic motivation over extrinsic, and highlighting impactful techniques like writing groups. Implications include providing training focusing on intrinsic rewards, developing programs for collaborative practices shown effective, and establishing an online community for continuous skills development and motivation. This study provides insights into optimally supporting Arab EFL instructors through initiatives prioritizing intrinsic motivators and interactive strategies demonstrated to engage learners.